Zingerone suppresses cell proliferation via inducing cellular apoptosis and inhibition of the PI3K/AKT/mTOR signaling pathway in human prostate cancer PC‐3 cells. Issue 1 (9th September 2020) - Qian, Shengqiang; Fang, Huiying; Zheng, Lu; Liu, Mei
Abstract: Prostate cancer (PCa) is both the foremost and second cause of cancer death in the male population. Patients with hormone‐dependent PCa are initially sensitive to androgen‐deprivation therapy, later the cancer progress to a hormone‐independent state and fails to respond and progress to the metastatic stage, where the cells gain the ability to escape cell death and develop resistance to current therapies, thereby leading to migration, invasion, and metastasis of cancer. Many clinical trials using nutraceuticals on cancer using human subjects have also been extensively studied, these studies confirm the efficacy of drugs tested in in vitro and in vivo preclinical models. Among various dietary phytochemicals, ginger is commonly used in the diet and possesses many active principles that act against cancer. Among various active principles, zingerone is a key active phenolic compound present in Zingiber officinale (Ginger), it has potent antioxidant property and it acts against carcinogens. The present study evaluated the efficacy of zingerone at different doses on the PCa cell line regarding apoptosis, upstream signing molecules such as Akt/mTOR, and migration metastasis. A cell viability assay using MTT was performed to estimate the percentage of viability of zingerone‐treated PC‐3 cells. The mitochondrial membrane potential, intracellular reactive oxygen species, and apoptosis induction in the zingerone‐treated PC‐3 cells were studied by using different fluorescence staining techniques. The expression patterns of PI3K, AKT, p‐AKT, mTOR, and p‐mTOR were investigated through the Western blot analysis assay. Zingerone induces apoptosis and alters Akt/mTOR molecules; it also inhibits cell adhesion and migration of PCa cells. From the present study, it is concluded that zingerone effectively induces apoptosis and inhibits cancer signaling, thereby acting as a potent drug against PCa.